Compound kushen injection improves radiation enteritis via cannabinoid receptor 1 in rats - Wenjing Xu; Liping Gao; Wenjuan Zou; Xiaohui Tang; Weiqi Nian; Weiqin Zheng; Rongzhong Huang; Pei Wang (BMC Complementary Medicine and Therapies)
Abstract Background Clinical studies have shown that Compound Kushen Injection (CKI) can alleviate the inflammatory symptoms of radiation enteritis. However, the mechanism of action remains unclear. The aim of this study was to explore the possible targets and mechanisms of CKI in the treatment of radiation enteritis. Methods Network pharmacology was used to predict the potential targets of CKI for the treatment of radiation enteritis, and GO and KEGG enrichment analyses were subsequently performed. SD rats were randomly divided into one of the following groups: control, model, CB1 agonist, CKI and CKI + CB1 antagonist. Except for the control group, the remaining groups were irradiated the abdomen with 6 MV medical high-energy x-ray linear accelerator to establish the model of radiation enteritis. After one week of treatment, the expression of inflammatory factors, SOD and GSH-Px activities, MDA, ROS and NO contents; NF-κB signaling activation and the expression of NOX4, CB1, p38 MAPK, p-p38 MAPK in the ileal tissues of rats were examined to assess the therapeutic effect and possible mechanism of CKI on radiation enteritis, respectively. Results According to network pharmacology, CB1 might be a target of CKI. GO and KEGG enrichment analyses revealed that CKI was significantly enriched in analgesic, endocannabinoid and inflammatory pathways. In the rat model, Compared with that in the radiotherapy group, the extent of ileal injury was significantly improved in the CKI group compared to the control group. In addition, the infiltration of CD68 and CD16b was significantly reduced, and the expression of MCP1, TNF-α, IL-1β and IL-10 was significantly decreased. In addition, the activities of SOD and GSH-Px were increased, and the activities of MDA, ROS and NO were decreased. The CKI group also showed inhibition of NF-κB signaling and a significant decrease in the expression of NOX4, CB1 and p-p38 MAPK/p38 MAPK. The use of a CB1 agonist could also alleviate radiation enteritis, whereas the addition of a CB1 antagonist could interfere with the ameliorative effect of CKI on radiation enteritis. Conclusions CKI might exert an anti-radiation enteritis effect by targeting the cannabinoid receptor 1.